Hidden San Francisco : a guide to lost landscapes, unsung heroes, and radical histories - Carlsson, Chris, 1957- (Pluto Press, 2020)
A radical, alternative guidebook to the history of San Francisco, complete with maps detailing walking and bike routes around the city.